2004
DOI: 10.1002/elps.200305952
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression analysis of an integrin family of genes by systematic multiplex reverse transcription‐polymerase chain reaction

Abstract: We have established the systematic multiplex reverse transcription-polymerase chain reaction (SM RT-PCR) system of 26 members of the integrin family of genes, and used this system to investigate their expression in 25 different kinds of human adult tissues. A hierarchical clustering analysis of the tissue expression data illustrated clustering of functionally related tissues. Although the correlation was weak, bone marrow, thymus, and spleen were clustered, potentially confirming the role of certain integrin m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…We prepared cDNA by reverse-transcription using oligo dT primers and the Advantage RT-for-PCR Kit (BD Biosciences-Clontech). We followed the SM RT-PCR experimental protocols described previously [29], [50], [51], [52]. Complementary DNA samples were used as templates to examine gene expression.…”
Section: Methodsmentioning
confidence: 99%
“…We prepared cDNA by reverse-transcription using oligo dT primers and the Advantage RT-for-PCR Kit (BD Biosciences-Clontech). We followed the SM RT-PCR experimental protocols described previously [29], [50], [51], [52]. Complementary DNA samples were used as templates to examine gene expression.…”
Section: Methodsmentioning
confidence: 99%
“…We then developed the SM RT-PCR systems of 39 human Hox genes [14] and 26 human integrin subunit genes [15]. Using these systems, we have demonstrated that SM RT-PCR is a useful method of semiquantitative quantification.…”
Section: Introductionmentioning
confidence: 99%
“…During the past several years, we have been developing a novel technique for semiquantitative quantification of gene expression named systematic multiplex reverse transcription-PCR (SM RT-PCR) [13][14][15]. SM RT-PCR is distinguishable from standard multiplex RT-PCR because it utilizes primers that amplify sequences that fall within a single exon of genes.…”
Section: Introductionmentioning
confidence: 99%
“…In mammals, 18 α and 8 β subunits combine to form 24 integrins [ 1 ]. Alternative splicing [ 2 ] and post-translational modifications [ 3 ] ensure a high diversity in integrin structure. Such diversity in subunit composition contributes to their expanded ligand recognition, binding to the extracellular matrix (ECM), and coupling to downstream signaling pathways [ 4 , 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%